Voluntary Wheel Running Partially Attenuates Early Life Stress-Induced Neuroimmune Measures in the Dura and Evoked Migraine-Like Behaviors in Female Mice - Eller, Olivia C.; Yang, Xiaofang; Fuentes, Isabella M.; Pierce, Angela N.; Jones, Brittni M.; Brake, Aaron D.; Wang, Ruipeng; Dussor, Gregory; Christianson, Julie A. (Frontiers in Physiology, 2021)
Migraine is a complex neurological disorder that affects three times more women than men and can be triggered by endogenous and exogenous factors. Stress is a common migraine trigger and exposure to early life stress increases the likelihood of developing chronic pain disorders later in life. Here we used our neonatal maternal separation (NMS) model of early life stress to investigate whether female NMS mice have an increased susceptibility to evoked migraine-like behaviors and the potential therapeutic effect of voluntary wheel running. NMS was performed for three hours/day during the first three weeks of life and initial observations were made at 12 weeks of age after voluntary wheel running (Exercise, -Ex) or sedentary behavior (-Sed) for 4 weeks. Mast cell degranulation rates were significantly higher in dura mater from NMS-Sed mice, compared to either naïve-Sed or NMS-Ex mice. Protease activated receptor 2 (PAR2) protein levels in the dura were significantly increased in NMS mice and a significant interaction of NMS and exercise was observed for transient receptor potential ankyrin 1 (TRPA1) protein levels in the dura. Behavioral assessments were performed on adult (>8 weeks of age) naïve and NMS mice that received free access to a running wheel beginning at 4 weeks of age. Facial grimace, paw mechanical withdrawal threshold, and light aversion were measured following direct application of inflammatory soup (IS) onto the dura or intraperitoneal nitroglycerin (NTG) injection. Dural IS resulted in a significant decrease in forepaw withdrawal threshold in all groups of mice, while exercise significantly increased grimace score across all groups. NTG significantly increased grimace score, particularly in exercised mice. A significant effect of NMS and a significant interaction effect of exercise and NMS was observed on hindpaw sensitivity following NTG injection. Significant light aversion was observed in NMS mice, regardless of exercise, following NTG. Finally, exercise significantly reduced CGRP protein level in the dura of NMS and naïve mice. Taken together, these findings suggest that while voluntary wheel running improved some measures in NMS mice that have been associated with increased migraine susceptibility, behavioral outcomes were not impacted or even worsened by exercise.